The mediating effect of alexithymia between Avoidant/Restrictive Food Intake Disorder (ARFID) and suicidal ideation among a sample of Lebanese adults - Lea Abou Nader; Georgio Chammas; Michael Chammas; Feten Fekih-Romdhane; Souheil Hallit; Sahar Obeid (PLoS ONE, 2026)
Background Avoidant/Restrictive Food Intake Disorder (ARFID) is an underdiagnosed eating disorder consisting of food avoidance that is not related to body image concerns. New evidence suggests that individuals identified as having ARFID experience elevated suicidal ideations. This association could be mediated by alexithymia, described as having difficulty in recognizing or verbalizing emotions. Therefore, this study aimed to determine whether alexithymia mediates the link between ARFID symptoms and suicidal ideation among Lebanese adults. Methods Between September and December 2024, a cross-sectional study was conducted using snowball sampling technique. 396 Lebanese adults (mean age = 26.26) took an online Arabic survey. Results 40.7% of the participants had thoughts of suicide. Younger age, being unmarried, less physical activity, higher ARFID scores, and increased alexithymia were significantly associated with suicidal ideation. Alexithymia fully mediated the link between ARFID symptoms and suicidal ideation (indirect effect: Beta = 0.02; Boot SE = 0.01; Boot 95% CI 0.01, 0.04). There was a strong correlation between higher avoidant/restrictive food intake disorder and higher alexithymia. There was also a significant association between higher alexithymia and the presence of suicidal ideation. Finally, there was no association between avoidant/restrictive food intake disorder and suicidal ideation. Conclusion Our findings support alexithymia as a fundamental psychological process linking ARFID symptoms and suicidal ideation. Given the sociocultural stigma and limited mental health resources in Lebanon, clinicians should consider screening for alexithymia among individuals with eating disorders and suicidal thinking. Interventions that focus on emotions could therefore be used to reduce suicide risk in this vulnerable population.